Business Cycle Accounting For Chile - Soderling, Ludvig; Simonovska, Ina. (Washington, D.C. : International Monetary Fund, 2008)
We investigate sources of economic fluctuations in Chile during 1998-2007 within the framework of a standard neoclassical growth model with time-varying frictions (wedges). We analyze the relative importance of efficiency, labor, investment, and government/trade wedges for business cycles in Chile. The purpose of this exercise is twofold: (i) focus the policy discussion on the most important wedges in the economy; and (ii) identify which broad class of models would present fruitful avenues for further research. We find that different wedges have played different roles during our studied period, but that the efficiency and labor wedges have had the greatest impact. We also compare our results with existing studies on Argentina, Brazil, and Mexico.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet